Consumption heterogeneity by occupation: Understanding the impact of occupation on personal consumption during the COVID-19 pandemic - Christopher D. Cotton; Vaishali Garga; Justin Rohan (Federal Reserve Bank of Boston, 2020)
This paper exploits the variation in the unemployment rate of different occupations in the first part of the COVID-19 pandemic to analyze the response of consumption spending to unemployment risk. We find that earlier in the pandemic, higher unemployment risk did not reduce relative spending. However, as the pandemic proceeded, higher unemployment risk reduced relative spending. This pattern held across both essential and nonessential spending categories. We find that "high-risk" occupations had three common characteristics: lower ability to be performed from home, higher physical proximity on the job, and a nonessential nature.
Keywords: E21; E32; E62; 330; consumption; occupation; unemployment risk; COVID-19; CARES Act